Increased risk of low birth weight in women with placental malaria associated with P. falciparum VAR2CSA clade - Jaymin C. Patel; Nicholas J. Hathaway; Christian M. Parobek; Kyaw L. Thwai; Mwayiwawo Madanitsa; Carole Khairallah; Linda Kalilani-Phiri; Victor Mwapasa; Achille Massougbodji; Nadine Fievet; Jeffery A. Bailey; Feiko O. ter Kuile; et al. (Scientific Reports, 2017)
Abstract Pregnancy associated malaria (PAM) causes adverse pregnancy and birth outcomes owing to Plasmodium falciparum accumulation in the placenta. Placental accumulation is mediated by P. falciparum protein VAR2CSA, a leading PAM-specific vaccine target. The extent of its antigen diversity and impact on clinical outcomes remain poorly understood. Through amplicon deep-sequencing placental malaria samples from women in Malawi and Benin, we assessed sequence diversity of VAR2CSA’s ID1-DBL2x region, containing putative vaccine targets and estimated associations of specific clades with adverse birth outcomes. Overall, var2csa diversity was high and haplotypes subdivided into five clades, the largest two defined by homology to parasites strains, 3D7 or FCR3. Across both cohorts, compared to women infected with only FCR3-like variants, women infected with only 3D7-like variants delivered infants with lower birthweight (difference: −267.99 g; 95% Confidence Interval [CI]: −466.43 g,−69.55 g) and higher odds of low birthweight (<2500 g) (Odds Ratio [OR] 5.41; 95% CI:0.99,29.52) and small-for-gestational-age (OR: 3.65; 95% CI: 1.01,13.38). In two distinct malaria-endemic African settings, parasites harboring 3D7-like variants of VAR2CSA were associated with worse birth outcomes, supporting differential effects of infection with specific parasite strains. The immense diversity coupled with differential clinical effects of this diversity suggest that an effective VAR2CSA-based vaccine may require multivalent activity.